Pemaliq of Sexual Organ within the Culture of Sasak Community: Linguistic Anthropology Study (e-Journal of Linguistics, 2020)
The focus of this study is pemaliq (taboo) of sexual organs within theculture of the Sasak community. This research was conducted with theaims of finding certain words used as an evasion for sexual organs andinvestigating the Sasak community’s view through the expression ofevasion words. The data was collected by applying the method ofparticipant observation and in-depth interviews. The data analysisshowed that the evasion words used by the Sasak community for sexualorgans are words in the form of euphemisms: pepa (for male andfemale genitals) and also words in metaphorical form: anak cobek (formale genital), cobek tombong, and dompet (for female genital). TheSasak community believes the use of evasion words in communicationcan create a psychological comfort and will not make the speakers feelabashed
Keywords: Pemaliq; sexual organ